Political obligation and legitimacy Hobbes, Locke and Rousseau - Hernandez, Carolina G. (Quezon City U.P. Diliman Interactive Learning Center, 2006)
Second phase of the online lecture series for Social Science II: a general education course on the social, economic and political thought.
Lecture delivered on August 2, 2006.
Executive director, Celia Adriano ; Director, Grace Javier Alfonso ; Co-produced by, Office of the Vice President for Academic Affairs ; U.P. Open University Media Center ; Department of Electrical and Electronics Engineering ; U.P. Computer Center ; Department of Political Science, U.P. Diliman.
Series Lecturer: Carolina G. Hernandez ; Moderator: Malaya C. Ronas.
Keywords: Hobbes, Thomas -- 1588-1679 -- Congresses; Locke, John -- 1632-1704 -- Congresses; Rousseau, Jean-Jacques -- 1712-1778 -- Congresses; Social contract -- Congresses; Political obligation -- Congresses; Legitimacy of governments -- Congresses